The Impact of the Business Environment on the Business Creation Process - Klapper, Leora (2012)
New data from the 2008 World Bank Group Entrepreneurship Survey indicates a very strong and statistically significant relationship between entrepreneurship and a better business environment. Data for 100 countries on the number of total and newly registered corporations over an eight-year period (2000-2007) were collected directly from registrars of companies around the world. Data were also collected on the functioning and structure of business registries. Empirical evidence suggests that greater ease in starting a business and better governance are associated with increased entrepreneurial activity. After controlling for economic development (gross domestic product per capita), higher entrepreneurial activity is significantly associated with cheaper, more efficient business registration procedures and better governance. Although the degree of progress in the modernization of business registries varies greatly, countries usually have a common goal to evolve from a paper-based business registry to a one-stop, automated, web-enabled registry capable of delivering products and services online via transactions involving authenticated users and documents. Tests show that business registry modernization (often a component of broader private sector reforms) has a positive impact not only on the ease of creating a business, but also on new business registration. Overall, the data show that a quick, efficient, and cost-effective business registration process is critical for fostering formal sector entrepreneurship.